Dynamical Effect Investigations of Component’s Internal Interface by Using Techniques of Rigid-Flex Coupling Simulation - Te-te Li (Hindawi Limited, 2021)
As a component of servicing car body, the internal interfaces of aluminum alloy carbody include all connections of equipments hanged under floor and mounted on roof, which are expected to form the weak coupling relationship. For an imported prototype with primary hunting phenomenon, a dynamical design methodology of speeding-up bogies was proposed. The analysis graph of full-vehicle stability properties and variation patterns is used to clarify a self-adaptive improvement direction, i.e., λeN ≥ λemin, and λemin = (0.03–0.05). Therefore, the central hollow tread wear can be self-cleaned in time or regularly by crossing over the dedicated lines of different speed-grades. The modified strategy with strong/weak internal interface transaction of servicing car body was furthermore formulated based on the dynamical condensation method of component interface displacements. The causal relationship between bogie vibration alarm and car body fluttering phenomenon was then demonstrated by using techniques of rigid-flex coupling simulation. The self-excited vibration of traction converter intersects with the unstable hunting oscillation, ca. 9.2/9.3 Hz, which is consistent with the conclusions of tracking-test investigations on two car body fluttering formations. The technical space to promote the construction speed is thereby lost completely because of ride comfort decline, unsafe vibration of onboard electrical equipments, and weld fatigue damage of aluminum alloy car body. However, the rigid-flex coupling simulation analyses of trailer TC02/07 confirm that the safety threshold of bogie vibration warning can be appropriately increased as long as the lateral modal frequency of traction converters is greater than 12 Hz, preferably close to 14 Hz.